2020
DOI: 10.3847/1538-4357/ab700a
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Molecular Gas Distribution in the M17 Cloud Complex: Dense Gas Conditions of Massive Star Formation?

Abstract: The non-uniform distribution of gas and protostars in molecular clouds is caused by combinations of various physical processes that are difficult to separate. We explore this non-uniform distribution in the M17 molecular cloud complex that hosts massive star formation activity using the 12 CO (J = 1−0) and 13 CO (J = 1 − 0) emission lines obtained with the Nobeyama 45m telescope. Differences in clump properties such as mass, size, and gravitational boundedness reflect the different evolutionary stages of the M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 109 publications
1
20
1
Order By: Relevance
“…Increasing HCN-to-HCO + ratios with increasing infrared luminosity have been found in LIRGs (Papadopoulos 2007). In the Galaxy, more evolved HII regions also show higher HCN-to-HCO + ratios than infrared dark clouds (Nguyen-Luong et al 2020). However, in our data, we do not see any trend of HCN-to-HCO + ratios against the L bol spanning four orders of magnitude.…”
Section: Variations Of Molecular Line Luminosity Ratioscontrasting
confidence: 80%
See 1 more Smart Citation
“…Increasing HCN-to-HCO + ratios with increasing infrared luminosity have been found in LIRGs (Papadopoulos 2007). In the Galaxy, more evolved HII regions also show higher HCN-to-HCO + ratios than infrared dark clouds (Nguyen-Luong et al 2020). However, in our data, we do not see any trend of HCN-to-HCO + ratios against the L bol spanning four orders of magnitude.…”
Section: Variations Of Molecular Line Luminosity Ratioscontrasting
confidence: 80%
“…The line ratio of HCN-to-HCO + seems to be sensitive to environments (Pety et al 2017;Shimajiri et al 2017). High HCN-to-HCO + ratios have been found in far-UV irradiated environments such as evolved Galactic HII regions (Nguyen-Luong et al 2020), AGNs (Aladro et al 2015) or luminous infrared galaxies (LIRGs; Papadopoulos 2007). This implies that HCO + abundance is sensitive to the ionization degree of molecular gas.…”
Section: Variations Of Molecular Line Luminosity Ratiosmentioning
confidence: 99%
“…In contrast, Povich et al (2016) interpreted that this core might be a foreground object and the main structure of M17 SWex may be located to 2 kpc. Recently we analyzed the cloud structures in this area using the wide-field 12 CO, 13 CO, and C 18 O observations (Shimoikura et al 2019;Nguyen-Luong et al 2020), and found that the molecular gas in the M17 and M17 SWex regions is continuous in the position-position velocity space, which is consistent with the argument of Povich et al (2016). Thus, in this paper, we adopt a distance to M17 SWex of 2 kpc.…”
Section: Introductionsupporting
confidence: 72%
“…The details of the observations are described by Shimoikura et al (2019), Nakamura et al (2019) and Nguyen-Luong et al (2020). In brief, we carried out mapping observations in 12 CO (J = 1 − 0) and 13 CO (J = 1 − 0) toward the M17 region using the FOREST receiver (Minamidani et al 2016) installed on the 45 m telescope of the Nobeyama Radio Observatory.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation